Critical review of the international and contractual measures for optimal restructuring. Issue 4 (1st October 2020) - Rahman, Ferdous
Abstract : Due to time constrain and uncertainties in getting payment through litigation, the sovereign creditors and the debtor prefer restructuring to litigation upon default. However, all the creditors may not agree on restructuring. Some of them may go for enforcement despite the detrimental effects on the restructuring process. After the experience of the sovereign debt crisis in several states, many legislative and contractual proposals were submitted and none of them achieved the desired success. This paper explores the challenges of the restructuring process and the national and international initiatives to mitigate these obstacles, especially the Collective Action Clauses (CACs). The findings express a skeptical view of the effectiveness of CACs to reduce the impediments in the restructuring process. Its overriding effect of majority debtholders' decisions on exit or stay increases the borrowing costs for the state because of the decrease in the independent decision-making power of the creditors.